Consensus and controversies regarding follow‐up after treatment with curative intent of nonmetastatic colorectal cancer: a synopsis of guidelines used in countries represented in the European Society of Coloproctology. (3rd January 2019) - Bastiaenen, V. P.; Hovdenak Jakobsen, I.; Labianca, R.; Martling, A.; Morton, D. G.; Primrose, J. N.; Tanis, P. J.; Laurberg, S.; ,
Abstract: Aim: It is common clinical practice to follow patients for a period of years after treatment with curative intent of nonmetastatic colorectal cancer, but follow‐up strategies vary widely. The aim of this systematic review was to provide an overview of recommendations on this topic in guidelines from member countries of the European Society of Coloproctology, with supporting evidence. Method: A systematic search of Medline, Embase and the guideline databases Trip database, BMJ Best Practice and Guidelines International Network was performed. Quality assessment included use of the AGREE‐II tool. All topics with recommendations from included guidelines were identified and categorized. For each subtopic, a conclusion was made followed by the degree of consensus and the highest level of evidence. Results: Twenty‐one guidelines were included. The majority recommended that structured follow‐up should be offered, except for patients in whom treatment of recurrence would be inappropriate. It was generally agreed that clinical visits, measurement of carcinoembryoinc antigen and liver imaging should be part of follow‐up, based on a high level of evidence, although the frequency is controversial. There was also consensus on imaging of the chest and pelvis in rectal cancer, as well as endoscopy, based on lower levels of evidence and with a level of intensity that was contradictory. Conclusion: In available guidelines, multimodal follow‐up after treatment with curative intent of colorectal cancer is widely recommended, but the exact content and intensity are highly controversial. International agreement on the optimal follow‐up schedule is unlikely to be achieved on current evidence, and further research should refocus on individualized 'patient‐driven' follow‐up and new biomarkers.